Pemertahanan Bahasa Sasak pada Masyarakat Kelurahan Kekalik Kebon Kota Mataram - Halimatussoleha, Siti; Anograjekti, Novi; Anwar, Miftahul Khairah (Jurnal Ilmiah Global Education, 2025)
This study aims to determine the condition of Sasak language usage, attitudes toward Sasak language preservation, and factors influencing attitudes toward Sasak language preservation. The method used in this study is qualitative descriptive research with the research subjects being the Sasak tribe community in Mataram District, Kekalik Kebon Village, Mataram City, NTB. The data consists of words or sentences obtained from research informants. The data sources in this study were the native speakers of the Kekalik Kebon neighborhood, Mataram District, Mataram City, through interviews with the native speakers. Additionally, direct observations were conducted in the field to observe the language usage. The data was analyzed using interactive analysis, which includes data reduction, data presentation, and drawing conclusions. Based on the results of the data analysis, it can be concluded that (1) the Sasak language is still used by the Kekalik Kebon community, although teenagers and children often use a mixture of Sasak and Indonesian  (2) The attitude toward the preservation of the Sasak language is by preparing the mindset or behavior and thoughts of the community in Mataram District, particularly in the Kekalik Kebon area, to use the Sasak language more dominantly when communicating. (3) The factors influencing the attitude toward the use of the Sasak language in Mataram District, Kekalik Kebon area, are age, atmosphere, and topic.